Shoot multiplication from shoot tip of F1 hybrid okra (Abelmoschus esculentus) by using different concentration of 6-benzylaminopurine (BAP) - Mohd Amirol, Norsafina (2017)
Okra (Abelmoschus esculentus L. Moench) belongs to Malvaceae family is an economically important vegetable crop grown in tropical and sub-tropical parts of the world. This research was conducted to determine the best 6-benzylaminopurine (BAP) for shoot multiplication from shoot tip explants of F1 hybrid okra (Abelmoschus esculentus). Seeds of F1 hybrid okra were germinated on Murashige and Skoog (MS) medium without addition any of plant growth regulator. In this study, shoot tips were excised from the 2 weeks old germinated seedlings and then cultured vertically in MS medium supplemented with different concentration of BAP (0 mg/L, 0.5mg/L, 1.0mg/L, 2.0mg/L, 5.0mg/L and 10.0mg/L). The media containing 2.0mg/L of BAP show the highest shoot multiplication of shoot tip culture of Abelmoschus esculentus with 7.6 shoot produced per explant after 5 weeks of culture.